Implementasi Bimbingan Konseling Dalam Merubah Perilaku Siswa SD Negeri 01 Dayu Gondangrejo Karanganyar - Ulfah, Laila Tiara, Minsih S.Ag, M.Pd (2017)
This study aims to describe: (1) implementation of unseling guidance in SD Negeri 01 Dayu in changing student behavior, (2) role of teacher and principal on implementation unseling guidance in changing student behavior in SD Negeri 01 Dayu. This research is a qualitative research. The subjects of this study were principals, teachers, and students. Data collection techniques used are observation techniques, interviews, documentation. Analytical techniques used consisted of three components of analysis, namely data reduction, data presentation, and withdrawal of conclusions or verification. This research begins with the preparation stage, the implementation of research, the preparation of reports and ending with reporting. The result of this research is the implementation of counseling guidance in SD Negeri 01 Dayu done through stage ofplanning,implementation, evaluation, and follow up. Students who have poor behavior are advised, guided and directed byindividual approaches done by principals and teachers, so that later can be formed good behavior,develop its potential and directed talent and interest of students. Implementation of thiscounseling guidance can also solve problems faced by students at school and at home.Keyword: guidedance and counseling, behavior, role of teacher and principal